Walking in the Forest: Understanding Spaces Through Cartography in the New-Generation Malayalam Cinema - Kavya, E.M. (Literary Studies, 2024)
Cinema as an audio-visual medium is vested in the significant and realistic portrayal of multiple spaces through the depiction of the city, countryside, houses, buildings, forest, etc. Malayalam cinema has a long history of dealing with forest spaces from livelihood to spaces of resort. This paper is an attempt to understand the new-generation Malayalam cinema’s engagement with space, especially forest spaces. It argues that new-generation Malayalam cinema tries to map forest spaces using the subjective understanding of the inhabitants with the help of narrative cartography. Walking in the forest will be the major technique in mapping the spaces. It also tries to unravel how the “representational spaces” (Lefebvre 38) have been delineated in the “representations of space” (38) through the subjective understanding of the “spatial practices” (38) in the movies. Human traversal through space in time mapping the spaces by following subjective histories and oral narratives will be looked upon. A detailed analysis of two movies, Churuli (2021) by Lijo Jose Pellissery and Virus (2018) by Aashiq Abu will be utilized in theorizing the “diegetic” (Steffen 25) space of the movies, taking the “natural space” (Lefebvre 30) of the forest into consideration. Key concepts in Spatial Literary Studies, importantly Henry Lefebvre’s The Production of Space and the idea of “heterotopia” (Foucault 24) introduced by Michel Foucault in his essay “Of Other Spaces: Utopias and Heterotopias” will be utilized in comprehending these movies.